An exploration of e-impulse buying. (2019) - Verma, Hemraj; Singh, Shalini
E-tailing is at nascent stage in India but it is already creating a difference in the manner consumers are behaving. Since e-impulse buying is a new phenomenon in Indian context therefore a qualitative approach through conducting interviews has been adopted to explore it deeply. This research reveals several stimuli (majorly - intrinsic stimuli and extrinsic stimuli) of e-impulse buying in Indian context and develops a platform for studying the phenomenon comprehensively. This study explored the phenomenon of e-impulse buying and also uncovered its relevant stimuli thus it may benefit the market researchers, strategists and online retailers for understanding the nitty-gritty of the phenomenon. This study is completely based on the exploratory approach that reveals several significant insights related to stimuli of e-impulse buying in a comprehensive way. It provides knowledge value to the researchers, academicians and online strategist to optimise their strategies in a better way.